Comparative efficacy of hydroxychloride and organic sources of zinc, copper, and manganese on hatching eggs, embryo and hatchlings attributes - Reza Bakhshalinejad; Stephanie Torrey; Elijah G. Kiarie (Poultry Science)
The objective of this study was to evaluate the impact of feeding broiler breeders hydroxychloride and organic sources of zinc (Zn), copper (Cu), and manganese (Mn) on hatching eggs, embryo, and hatchlings attributes. A total of 408 female (♀) and 48 male (♂) Ross 708 broiler breeder were placed (17 ♀ and 2 ♂/pen). The pens were housed in two rooms (12 pens/room). Two diets were allocated to 12 replicates/diet using completely randomized block design. The two diets were formulated to have similar nutritional specifications and differed in the sources of Zn, Cu, and Mn: 1) HO, a blend of 80 % hydroxychloride and 20 % proteinate organic sources, and 2) OR, 100 % amino acid complex organic sources. The birds were fed from 42 to 63 weeks of age following breeder guidelines. A total of 90 eggs were collected from each pen over 10 consecutive days at 46, 54, and 62 weeks of age. Six eggs per pen were sampled prior to incubation and during d 14 and 19 of incubation for analyses. At hatch, 3 male and 3 female chicks were randomly selected from each pen, bled for plasma concentration of minerals and subsequently euthanized for liver and gizzard weight. There were no interactions (P > 0.05) between the breeder age and trace mineral sources or main effects of trace mineral sources on egg components, settable egg percentage, fertility, hatchability, late-embryonic mortality, and the ratio of hatched male to female. However, eggs from breeder fed HO diets had heavier eggshells compared to those fed OR diets (P = 0.003). Regardless of trace mineral sources, chicks from older hens had higher (P < 0.05) plasma concentration of Zn, Cu, Mn, compared to chicks from younger hens. In conclusion, with exception of eggshell weight, there were no differences of feeding mid to late lay broiler breeders HO or OR sources of Zn, Cu, and Mn on hatching egg, embryo and hatchling mineral status